Exposure to mental load and psychosocial risks in kindergarten teachers - Čecho Robert; Švihrová Viera; Čecho Dominika; Novák Martin; Hudečková Henrieta (Sciendo, 2019)
Published research studies in Central Europe have been mostly oriented toward occupational stress among schoolteachers. The aim of this study is to investigate the level of occupational stress in kindergarten teachers and to specify psychosocial risks associated with their work.